PENGEMBANGAN MEDIA POP UP BOOK BERBASIS LITERASI SAINS PADA MATERI SISTEM EKSKRESI SISWA KELAS VIII SMP - Adhe Winda Septiana; Mariani Natalina; Darmadi Darmadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to produce quality science literacy-based pop up books. This research was conducted at the Biology Education Laboratory of UR FKIP and SMPN 10 Pekanbaru in July 2020-February 2021. The type of research used is Research and Development (R&D). Media development is carried out according to the ADDIE model with the Analyze, Design, Development, Implementation, Evaluation stages. This research was only carried out until the Development stage by validating by validators and limited trial phase I by Biology Education Students, FKIP UR, and limited trial phase II by students of SMPN 10 Pekanbaru. The assessment of the pop up book media developed includes 5 aspects, namely aspects of content, language, presentation, overall appearance and scientific literacy. The mean result of validation based on scientific literacy gets a score of 3.60 in the very valid category. The mean results of the limited trial phase I get a score of 3.82 and stage II get a score of 3.83 in the very good category. Based on these data, it can be concluded that the science literacy-based pop up book media that has been developed are categorized as quality media and can be used on a large scale.Key Words: Pop Up Book, Science Literacy, Execression System